Mapping and Characterizing Instruments for Assessing Family Nurses' Workload: Scoping Review - António Dias; Beatriz Araújo; Élvio Jesus (MDPI AG, 2024)
Background: The importance of knowing the workload of family nurses lies essentially in the possibility of improving health outcomes, care processes and the nurse's professional life. There is a lack of studies that fully describe the nursing workload in primary care, particularly, in the context of family health nursing, and the ideal metrics to be used remain unknown, making it impossible to characterize and therefore provide the necessary insight to acknowledge the different contributions of several aspects that embody the global workload of family nurses. The objective of this scoping review was to map the known evidence and characterize the instruments used to assess the workload of family nurses. Methods: Scoping review, according to the Joanna Briggs Institute, proposed a methodology for scoping reviews, consisting of three research stages: (1) an initial research in Medline and CINHAL; (2) an extended search, using keywords and search terms, in the following databases: JBI, CINAHL Complete, MEDLINE, Cochrane and Scopus; and (3) a search of the reference lists of the selected articles. No time limit was defined. Results: Fourteen studies referring to ten assessment instruments were included. Nine of them analyze workload as a dimension of a broader instrument, and two studies refer to an instrument that focuses exclusively on workload. Conclusions: The diversity of professional competencies and contexts, the conceptual complexity of workload and the absence of a theoretical framework make it difficult to identify consensual instruments to assess the workload of family nurses. This study was prospectively registered with the Open Science Framework® on 6 September 2023, with the registration number: 3k6vr.